Gasoline engine tail gas purification three-way catalyst and preparation method thereof

By introducing Mg-Co-Ni-Fe active components into the gasoline engine exhaust purification catalyst to replace Ru, a three-way catalyst containing alumina and Ce-Zr composite oxides was prepared, solving the problems of high cost and safety of precious metals and achieving effective control of NH3 emissions.

CN120885238APending Publication Date: 2025-11-04CHONGQING VEHICLE TEST & RES INST CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511069422.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-31
Publication Date
2025-11-04

AI Technical Summary

Technical Problem

Existing three-way catalytic converters for gasoline engine exhaust purification suffer from the problems of high cost and safety associated with the precious metal Ru when treating NH3 emissions, and the insufficient oxidation performance of Pd and Rh for NH3, which can easily lead to side reactions.

Method used

A ternary catalyst containing alumina, Ce-Zr composite oxide, and Mg-Co-Ni-Fe active components was prepared by introducing Mg-Co-Ni-Fe active components into the catalyst coating to replace the noble metal Ru. NH3 emissions were reduced by coating the catalyst with a lower and upper coating layer on the support.

Benefits of technology

It effectively reduces the emission concentration of NH3 in exhaust gas, meets regulatory requirements, reduces catalyst costs, improves safety, and avoids the use of Ru.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure IMAGE_5BC2560D-C0EE-4FA7-A51F-24A05480A8E9
    Figure IMAGE_5BC2560D-C0EE-4FA7-A51F-24A05480A8E9
Patent Text Reader

Abstract

The invention discloses a gasoline engine tail gas purification three-way catalyst, which comprises a carrier and a coating coated on the carrier, the coating comprises a lower coating and an upper coating which are arranged in sequence, and the upper coating comprises alumina, a Ce-Zr composite oxide, an Mg-Co-Ni-Fe active component compound and a salt auxiliary agent. The Mg-Co-Ni-Fe active component composed of base metal is introduced into the coating of the catalyst, the emission concentration value of NH3 in waste gas can be greatly reduced under the condition that precious metal Ru is not used, the catalyst can more easily meet the emission limit value of NH3 in laws and regulations, the good ammonia treatment effect on internal combustion engines such as gasoline engines is achieved, and the service life of the catalyst is prolonged. Meanwhile, the cost of the catalyst is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application belongs to the technical field of catalysts, and particularly relates to a gasoline engine exhaust purification three-way catalyst and a preparation method thereof. BACKGROUND

[0002] At present, the gasoline engine exhaust purification catalyst is mainly a noble metal type catalyst, which is composed of four parts, namely, a cordierite honeycomb ceramic carrier as a coating layer, a high specific surface porous material as a noble metal dispersion base material, and noble metals Pt, Pd and Rh as active components. Among them, the Pd and Rh active components can efficiently catalyze the oxidation of CO and hydrocarbons, so that they are converted into harmless CO2 and H2O; Rh can catalyze NO x to be reduced to harmless N2. Since the above-mentioned catalyst can simultaneously treat CO, hydrocarbons and NO x three kinds of pollutants, it is also called a three-way catalyst.

[0003] The three-way catalyst will have a side reaction in the catalytic reaction, and the most typical one is that NO x is excessively reduced to NH3, which will bring certain harm to the human body and the environment. With the promulgation of the national six regulations for heavy-duty vehicles, natural gas engines are included in the category of NH3 emission control. It can be foreseen that the NH3 emission limit of gasoline engines will also be added to the emission regulations in the near future. Therefore, one of the current research focuses of the three-way catalyst is to control the emission of NH3; Pd and Rh have high activity for CO and hydrocarbons, but the oxidation performance of NH3 is insufficient, and side reactions are also easy to occur, such as excessive oxidation to N2O and NO pollutants.

[0004] One of the effective means to control the NH3 emission of internal combustion engines at present is to add Ru active component in the catalyst. Ru can efficiently catalyze the direct decomposition of NH3 into N2 and H2. But Ru also belongs to noble metal, and the price is relatively high. The use of Ru in addition to Pt / Pd / Rh three noble metals will greatly increase the cost of the catalyst, which is not conducive to economy. At the same time, one of the oxides of Ru, RuO4, is volatile and toxic, which is not conducive to safety in use. SUMMARY

[0005] The present application aims to at least solve one of the technical problems in the related art. To this end, the main purpose of the present application is to provide a gasoline engine exhaust purification three-way catalyst, which can effectively reduce the ammonia emission value in the exhaust gas by adding a low-cost Mg-Co-Ni-Fe active component in the coating layer of the catalyst, while avoiding the use of noble metal Ru, reducing the material cost of the catalyst, and improving the safety.

[0006] The application further provides a preparation method of the gasoline engine exhaust purification three-way catalyst.

[0007] The application aims to realize the following technical solutions. A gasoline engine exhaust purification three-way catalyst comprises a carrier and a coating layer coated on the carrier, the coating layer comprises a lower coating layer and an upper coating layer arranged in sequence, and the upper coating layer comprises alumina, a Ce-Zr composite oxide, a Mg-Co-Ni-Fe active component compound and a salt additive.

[0008] In some specific embodiments, the carrier is a cordierite honeycomb ceramic carrier, the lower coating layer comprises alumina, a Ce-Zr composite oxide and a salt additive, and the lower coating layer is loaded with a noble metal Pd or Pt; and the upper coating layer is loaded with a noble metal Rh.

[0009] In some specific embodiments, the loading amount of Ru metal in the upper coating layer is 1-6 g / ft 3 ; and the loading amount of the noble metal Pd or Pt in the lower coating layer is 40-60 g / ft 3 .

[0010] In some specific embodiments, the mass ratio of each element in the Mg-Co-Ni-Fe active component compound is 1:1-2:1-2:1-3 in sequence, and the mass percentage of the Mg-Co-Ni-Fe active component compound in the upper coating layer is 5-10%.

[0011] In some specific embodiments, the mass ratio of alumina, the Ce-Zr composite oxide, the Mg-Co-Ni-Fe active component compound and the salt additive in the upper coating layer is (30-45):(30-50):(5-15):(5-15).

[0012] The mass ratio of alumina, the Ce-Zr composite oxide and the salt additive in the lower coating layer is (50-60):(30-40):(5-15).

[0013] In some specific embodiments, the Ce-Zr composite oxide is a cerium-zirconium solid solution, and the cerium-zirconium solid solution comprises 20-70% of CeO2 in mass content.

[0014] In some specific embodiments, the alumina is gamma-alumina, and the specific surface area is 100-200 m 2 / g.

[0015] In some specific embodiments, the salt additive is one or more of the salts corresponding to Ba, La, Nd, Pr, Y, Sb and Ti elements.

[0016] As the same inventive concept, the application further provides a preparation method of a gasoline engine exhaust purification three-way catalyst, comprising the following preparation steps: Preparation and coating of the lower coating layer: alumina, Ce-Zr composite oxide and salt additives are prepared into a raw slurry and placed in a container for stirring, a soluble solution containing noble metals is added, stirring is performed for 0.5-2 hours, a catalyst lower coating slurry is obtained, the lower coating slurry is coated on a carrier, and drying and calcination are performed to obtain a semi-finished catalyst; Preparation of the Mg-Co-Ni-Fe active component compound: according to the mass ratio of each element in the Mg-Co-Ni-Fe compound, soluble salts of Mg, Co and Fe are mixed and dissolved in deionized water to form a solution, an organic base is added to the solution to precipitate Mg, Co and Fe completely, then soluble salts of nickel are added according to the proportion, the mixture is uniformly stirred, and then the mixture is placed in a microwave oven for drying to form a Mg-Co-Ni-Fe powder compound; (3) Preparation and coating of the upper coating layer: alumina, Ce-Zr composite oxide, Mg-Co-Ni-Fe powder compound and salt additives are prepared into a raw slurry and placed in a container for stirring, a soluble solution containing noble metals is added, stirring is performed for 0.5-2 hours, a catalyst upper coating slurry is obtained, the upper coating slurry is coated on the semi-finished catalyst prepared in step (1), and drying and calcination are performed to finally obtain a finished catalyst.

[0017] In some specific embodiments, the soluble solution containing noble metals in step (1) is a salt solution of Pd or Pt, and the soluble solution containing noble metals in step (3) is a salt solution of Rh.

[0018] In some specific embodiments, the drying and calcination in steps (1) and (3) is performed at 120-180℃ for 2-3 hours, and then at 400-650℃ for 2-3 hours.

[0019] Compared with the prior art, the application has at least the following advantages: The application introduces the Mg-Co-Ni-Fe active component composed of base metals into the coating layer of the catalyst, which can greatly reduce the emission concentration value of NH3 in the exhaust gas without using the noble metal Ru, so that the catalyst can more easily meet the emission limit value of NH3 in the regulations, has a good ammonia treatment effect on internal combustion engines such as gasoline engines, and the cost of the catalyst is reduced. DETAILED DESCRIPTION

[0020] The application will be further described in detail below in combination with specific examples, which are only descriptive and not limiting, and cannot limit the protection scope of the application.

[0021] When a range, preferably range, or preferred upper and lower limits of a numerical value are stated as a form of expression of a certain amount, concentration or other value or parameter, it should be understood that any range formed by combining any pair of upper or preferred numerical values with any lower or preferred numerical value is specifically disclosed, regardless of whether the range is specifically disclosed. Unless otherwise indicated, the numerical value ranges listed herein include the endpoints of the range, and all integers and fractions within the range.

[0022] Unless otherwise indicated, all percentages, parts, ratios, etc. herein are by weight.

[0023] The materials, methods, and examples herein are illustrative only and, except as specifically stated, are not to be construed as limitations.

[0024] Example 1 The present embodiment provides a preparation method of a gasoline engine exhaust purification three-way catalyst, in particular: A gasoline engine exhaust purification three-way catalyst comprises a cordierite honeycomb ceramic carrier; the carrier is coated with a coating layer, the coating layer comprises a lower coating layer and an upper coating layer, and the coating amount of the lower coating layer and the upper coating layer is 100 g / L. The lower coating layer comprises 60% alumina, 30% Ce-Zr composite oxide and 10% BaO, and simultaneously loaded with 50 g / ft 3 of Pd.

[0025] The upper coating layer comprises 40% alumina, 50% Ce-Zr composite oxide, 5% Mg-Co-Ni-Fe active component compound and 5% La2O3, and simultaneously loaded with 5 g / ft 3 of Rh.

[0026] The specific surface area of the alumina in the lower coating layer is 100 m 2 / g, the content of CeO2 in the Ce-Zr composite oxide is 70%, the specific surface area of the alumina in the upper coating layer is 100 m 2 / g, the content of CeO2 in the Ce-Zr composite oxide is 20%, and the mass ratio of each element in the Mg-Co-Ni-Fe active component compound in the upper coating layer is 1:1:1:1.

[0027] The preparation steps of the catalyst are as follows: Preparation and coating of the lower coating layer: alumina, Ce-Zr composite oxide and barium acetate are mixed according to the coating ratio, and deionized water is added to prepare a raw slurry which is placed in a container for stirring. Pd nitrate solution is added, and stirring is performed for 0.5 h to obtain a catalyst lower coating layer slurry. The lower coating layer slurry is coated on the carrier, and dried at 120°C for 2 h and calcined at 400°C for 2 h to obtain a semi-finished catalyst; Preparation of Mg-Co-Ni-Fe active component compound: according to the mass ratio of each element in the Mg-Co-Ni-Fe compound, magnesium nitrate, cobalt nitrate and iron nitrate were mixed and dissolved in deionized water to form a solution, ethanolamine was added to the above solution to precipitate Mg, Co and Fe completely, then nickel acetate was added according to the proportion, the above mixture was placed in a microwave oven after uniform mixing and stirring, and Mg-Co-Ni-Fe powder compound was formed; Preparation and coating of upper coating layer: alumina, Ce-Zr composite oxide, Mg-Co-Ni-Fe powder compound and lanthanum nitrate were mixed according to the coating ratio to prepare a slurry, which was placed in a container for stirring, Rh nitrate solution was added, stirring was carried out for 0.5 h, and an upper coating layer slurry of the catalyst was obtained. The upper coating layer slurry was coated on the semi-finished catalyst prepared in step (1), and was dried at 180℃ for 3 h and calcined at 650℃ for 3 h to obtain a finished catalyst.

[0028] Example 2: The embodiment provides a preparation method of a gasoline engine exhaust purification three-way catalyst. A gasoline engine exhaust purification three-way catalyst comprises a cordierite honeycomb ceramic carrier with a specification of Ф132.1 mm×127 mm, a pore density of 750 cpsi, a pore wall thickness of 4.3 mil and a volume of 1.741 L. A coating layer is coated on the carrier, and the coating layer comprises a lower coating layer and an upper coating layer. The coating amount of the lower coating layer and the upper coating layer is 100 g / L respectively. The lower coating layer comprises 55% of alumina, 35% of Ce-Zr composite oxide and 10% of Nd2O3, and simultaneously loads 50 g / ft 3 of Pt; the upper coating layer comprises 45% of alumina, 35% of Ce-Zr composite oxide, 10% of Mg-Co-Ni-Fe active component compound and 10% of Pr6O 11 , and simultaneously loads 5 g / ft 3 of Rh.

[0029] The specific surface area of the alumina in the lower coating layer is 200 m 2 / g, the content of CeO2 in the Ce-Zr composite oxide is 60%, the specific surface area of the alumina in the upper coating layer is 200 m 2 / g, the content of CeO2 in the Ce-Zr composite oxide is 30%, and the mass ratio of each element in the Mg-Co-Ni-Fe active component compound in the upper coating layer is 1:2:1:1.

[0030] The preparation steps of the catalyst are as follows: (1) Preparation and coating of the lower coating layer: alumina, Ce-Zr composite oxide and neodymium nitrate were mixed according to the coating proportion, deionized water was added to prepare a slurry which was placed in a container for stirring, Pt nitrate solution was added, stirring was performed for 2 h, a catalyst lower coating layer slurry was obtained, the lower coating layer slurry was coated on the carrier, and drying was performed at 150℃ for 2 h, and calcination was performed at 500℃ for 2 h to obtain a semi-finished catalyst; (2) Preparation of the Mg-Co-Ni-Fe active component compound: according to the mass ratio of each element in the Mg-Co-Ni-Fe compound, magnesium chloride, cobalt acetate and iron nitrate were mixed to form a solution in deionized water, tetraethylammonium hydroxide was added to the above solution to precipitate Mg, Co and Fe completely, then nickel acetate was added according to the proportion, and the mixture was stirred uniformly, and then the above mixture was placed in a microwave oven for drying to form a Mg-Co-Ni-Fe powder compound; (3) Preparation and coating of the upper coating layer: alumina, Ce-Zr composite oxide, Mg-Co-Ni-Fe powder compound and praseodymium nitrate were mixed according to the coating proportion to prepare a slurry which was placed in a container for stirring, Rh nitrate solution was added, stirring was performed for 2 h, an upper coating layer slurry of the catalyst was obtained, the upper coating layer slurry was coated on the semi-finished catalyst prepared in step (1), and drying was performed at 150℃ for 3 h, and calcination was performed at 550℃ for 3 h to obtain a finished catalyst.

[0031] Example 3: The embodiment provides a preparation method of a gasoline engine exhaust purification three-way catalyst. A gasoline engine exhaust purification three-way catalyst includes a cordierite honeycomb ceramic carrier with a specification of Ф132.1 mm×127 mm, a pore density of 750 cpsi, a pore wall thickness of 4.3 mil, and a volume of 1.741 L; the carrier is coated with a coating layer, the coating layer includes a lower coating layer and an upper coating layer, and the coating amount of the lower coating layer and the upper coating layer is 100 g / L respectively. The lower coating layer contains 60% alumina, 30% Ce-Zr composite oxide and 10% Y2O3, and simultaneously loads 50 g / ft 3 of Pd; the upper coating layer contains 40% alumina, 40% Ce-Zr composite oxide, 10% Mg-Co-Ni-Fe active component compound and 10% Sb2O3, and simultaneously loads 5 g / ft 3 of Rh.

[0032] The specific surface area of the alumina in the lower coating layer is 150 m 2 / g, the content of CeO2 in the Ce-Zr composite oxide is 50%, and the specific surface area of the alumina in the upper coating layer is 140 m 2 / g, the content of CeO2 in the Ce-Zr composite oxide is 40%, and the mass ratio of each element in the Mg-Co-Ni-Fe active component compound in the upper coating layer is 1:2:2:1.

[0033] The preparation steps of the catalyst are as follows: (1) Preparation and coating of the lower coating layer: alumina, Ce-Zr composite oxide and yttrium nitrate are mixed according to the coating ratio, deionized water is added to prepare a slurry, and the slurry is placed in a container for stirring. Pd nitrate solution is added and stirred for 2 h to obtain a catalyst lower coating slurry. The lower coating slurry is coated on the carrier and dried at 160°C for 2 h and calcined at 450°C for 2 h to obtain a semi-finished catalyst; (2) Preparation of the Mg-Co-Ni-Fe active component compound: according to the mass ratio of each element in the Mg-Co-Ni-Fe compound, magnesium nitrate, cobalt acetate and iron nitrate are mixed to form a solution in deionized water. Tetraethylammonium hydroxide is added to the above solution to completely precipitate Mg, Co and Fe. Then, nickel nitrate is added according to the ratio, and the mixture is uniformly stirred and then placed in a microwave oven for drying to form a Mg-Co-Ni-Fe powder compound; (3) Preparation and coating of the upper coating layer: alumina, Ce-Zr composite oxide, Mg-Co-Ni-Fe powder compound and antimony acetate are mixed according to the coating ratio to prepare a slurry, which is placed in a container for stirring. Rh nitrate solution is added and stirred for 2 h to obtain a catalyst upper coating slurry. The upper coating slurry is coated on the semi-finished catalyst prepared in step (1) and dried at 160°C for 3 h and calcined at 500°C for 3 h to obtain a finished catalyst.

[0034] Example 4: The embodiment provides a preparation method of a gasoline engine exhaust purification three-way catalyst. A gasoline engine exhaust purification three-way catalyst includes a cordierite honeycomb ceramic carrier with a specification of Ф132.1 mm x 127 mm, a pore density of 750 cpsi, a pore wall thickness of 4.3 mil, and a volume of 1.741 L. The carrier is coated with a coating layer, which includes a lower coating layer and an upper coating layer. The coating amount of the lower coating layer and the upper coating layer is 100 g / L respectively. The lower coating layer contains 60% alumina, 30% Ce-Zr composite oxide and 10% TiO2, and simultaneously loads 50 g / ft 3 Pd. The upper coating layer contains 30% alumina, 50% Ce-Zr composite oxide, 10% Mg-Co-Ni-Fe active component compound and 10% La2O3, and simultaneously loads 5 g / ft 3 Rh.

[0035] The specific surface area of the alumina in the lower coating layer is 150 m2 / g, the content of CeO2 in the Ce-Zr composite oxide is 40%, the specific surface area of the alumina in the upper coating is 140 m 2 / g, the content of CeO2 in the Ce-Zr composite oxide is 60%, and the mass ratio of each element in the Mg-Co-Ni-Fe active component compound in the upper coating is 1:2:2:3.

[0036] The preparation steps of the catalyst are as follows: (1) Preparation and coating of the lower coating: alumina, Ce-Zr composite oxide and titanium tetrachloride are mixed according to the coating ratio, deionized water is added to prepare a slurry, and the slurry is placed in a container for stirring. Pd nitrate solution is added and stirred for 2 h to obtain a catalyst lower coating slurry. The lower coating slurry is coated on the carrier and dried at 160°C for 2 h and calcined at 450°C for 2 h to obtain a semi-finished catalyst. (2) Preparation of Mg-Co-Ni-Fe active component compound: according to the mass ratio of each element in the Mg-Co-Ni-Fe compound, magnesium nitrate, cobalt nitrate and iron nitrate are mixed to form a solution in deionized water. Tetramethylammonium hydroxide is added to the above solution to completely precipitate Mg, Co and Fe. Then, nickel nitrate is added according to the ratio, and the mixture is stirred uniformly. The above mixture is then placed in a microwave oven for drying to form a Mg-Co-Ni-Fe powder compound. (3) Preparation and coating of the upper coating: alumina, Ce-Zr composite oxide, Mg-Co-Ni-Fe powder compound and lanthanum nitrate are mixed according to the coating ratio to prepare a slurry, which is placed in a container for stirring. Rh nitrate solution is added and stirred for 2 h to obtain a catalyst upper coating slurry. The upper coating slurry is coated on the semi-finished catalyst prepared in step (1) and dried at 150°C for 3 h and calcined at 550°C for 3 h to obtain a finished catalyst.

[0037] Comparative Example 1: This comparative example provides a preparation method of a gasoline engine exhaust purification three-way catalyst, specifically: A gasoline engine exhaust purification three-way catalyst includes a cordierite honeycomb ceramic carrier with a specification of Ф132.1 mm x 127 mm, a pore density of 750 cpsi, a pore wall thickness of 4.3 mil, and a volume of 1.741 L. The carrier is coated with a coating layer, which includes a lower coating layer and an upper coating layer. The coating amount of the lower coating layer and the upper coating layer is 100 g / L respectively. The lower coating layer contains 60% alumina, 30% Ce-Zr composite oxide and 10% BaO, and simultaneously loads 50 g / ft 3 of Pd. The upper coating layer contains 40% alumina, 55% Ce-Zr composite oxide and 5% La2O3, and simultaneously loads 5 g / ft 3of Rh and 3 g / ft 3 of Ru.

[0038] The specific surface area of alumina in the undercoat is 100 m 2 / g, the CeO2 content in the Ce-Zr composite oxide is 70%, the specific surface area of alumina in the top coat is 100 m 2 / g, and the CeO2 content in the Ce-Zr composite oxide is 20%.

[0039] The preparation steps of the catalyst are as follows: (1) Preparation and coating of the undercoat: Mix alumina, Ce-Zr composite oxide and barium acetate according to the coating ratio, add deionized water to prepare a raw slurry, place it in a container and stir, add Pd nitrate solution, stir for 0.5 h to obtain the undercoat slurry of the catalyst. Coat the undercoat slurry on the carrier, dry it at 120°C for 2 h, and calcine it at 400°C for 2 h to obtain a semi-finished catalyst; (2) Preparation and coating of the top coat: Mix alumina, Ce-Zr composite oxide and lanthanum nitrate according to the coating ratio to prepare a raw slurry, place it in a container and stir, add Rh nitrate and Ru nitrate solutions, stir for 0.5 h to obtain the top coat slurry of the catalyst. Coat the top coat slurry on the semi-finished catalyst prepared in step (1), dry it at 180°C for 3 h, and calcine it at 650°C for 3 h to obtain the finished catalyst.

[0040] Comparative Example 2: This comparative example provides a preparation method of a three-way catalyst for purifying gasoline engine exhaust gas. Specifically: A three-way catalyst for purifying gasoline engine exhaust gas includes a cordierite honeycomb ceramic carrier with a specification of Ф132.1 mm×127 mm, a pore density of 750 cpsi, a pore channel wall thickness of 4.3 mil, and a volume of 1.741 L; a coating is coated on the carrier, and the coating includes an undercoat and a top coat, and the coating amounts of the undercoat and the top coat are each 100 g / L. The undercoat includes 60% alumina, 30% Ce-Zr composite oxide and 10% TiO2, and simultaneously loads 50 g / ft 3 of Pd; The top coat includes 35% alumina, 55% Ce-Zr composite oxide and 10% La2O3, and simultaneously loads 5 g / ft 3 of Rh.

[0041] The specific surface area of alumina in the undercoat is 150 m 2 / g, the CeO2 content in the Ce-Zr composite oxide is 40%, the specific surface area of alumina in the top coat is 140 m 2 / g, the CeO2 content in the Ce-Zr composite oxide is 60%.

[0042] The catalyst preparation steps are as follows: (1) Preparation and coating of the lower coating: Alumina, Ce-Zr composite oxide and titanium tetrachloride are mixed according to the coating ratio, deionized water is added to prepare the original slurry, and the slurry is placed in a container and stirred. Nitric acid Pd solution is added and stirred for 2 h to obtain the catalyst lower coating slurry. The lower coating slurry is coated on the carrier and dried at 160℃ for 2 h and calcined at 450℃ for 2 h to obtain the semi-finished catalyst. (2) Preparation and coating of the upper coating: Alumina, Ce-Zr composite oxide and lanthanum nitrate are mixed according to the coating ratio to prepare a raw slurry. The slurry is placed in a container and stirred. Nitric acid Rh solution is added and stirred for 2 h to obtain the catalyst upper coating slurry. The upper coating slurry is coated on the semi-finished catalyst obtained in step (1) and dried at 150°C for 3 h and calcined at 550°C for 3 h to obtain the finished catalyst.

[0043] Performance comparison test: The three-way catalysts prepared in Examples 1-4 and Comparative Examples 1-2 were encapsulated into exhaust purifiers and installed in the exhaust system of a 1.5 L displacement China VI light-duty gasoline vehicle (Category I vehicle) with a tight coupling. Then, a Type I test according to GB18352.6-2016 was conducted on a vehicle dynamometer to compare the typical fresh gaseous pollutant emissions of each scheme. Next, the catalysts from each scheme were installed on a gasoline engine test bench and aged using GMAC875 for 200 hours. After aging, the catalysts from each scheme were again installed in the exhaust system of the aforementioned 1.5 L displacement China VI light-duty gasoline vehicle, and a Type I test according to GB18352.6-2016 was conducted on a vehicle dynamometer to compare the typical fresh gaseous pollutant emissions of each scheme. The emission comparison test results are shown in Table 1.

[0044] Table 1 Comparison of gaseous pollutant emissions from each Scheme in Type I trials As shown in Table 1, the catalysts prepared using the methods in Examples 1-4 of this invention have low CO, THC, and NO content. x The fresh emissions were comparable to those of Comparative Examples 1-2, but the NH3 emissions were close to those of Comparative Example 1 with added Ru, and were on average more than 60% lower than those of the conventional scheme in Comparative Example 2. After bench aging, the catalyst emission values ​​of Examples 1-4 all met the requirements of China VI (b) regulations, and the NH3 emissions were still comparable to those of Comparative Example 1 with added Ru, while the NH3 emissions of the conventional scheme in Comparative Example 2 were on average more than twice as high as those of Examples 1-4. Therefore, the three-way catalyst provided by this invention can achieve effective control of NH3 emissions without the use of Ru.

[0045] The above embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit it. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention, and they should all be covered within the scope of the claims and specification of the present invention.

Claims

1. A three-way catalytic converter for purifying gasoline engine exhaust gases, characterized in that: The invention includes a carrier and a coating applied to the carrier. The coating comprises a lower coating and an upper coating arranged sequentially. The upper coating contains alumina, Ce-Zr composite oxide, Mg-Co-Ni-Fe active component compound, and salt additive.

2. The three-way catalytic converter for gasoline engine exhaust purification according to claim 1, characterized in that: The carrier is a cordierite honeycomb ceramic carrier, the lower coating contains alumina, Ce-Zr composite oxide and salt additives, and the lower coating is loaded with noble metal Pd or Pt; the upper coating is loaded with noble metal Rh.

3. The three-way catalytic converter for gasoline engine exhaust purification according to claim 2, characterized in that: The mass ratio of alumina, Ce-Zr composite oxide, Mg-Co-Ni-Fe active component compound and salt additive in the upper coating is (30-45):(30-50):(5-15):(5-15).

4. The three-way catalytic converter for gasoline engine exhaust purification according to claim 3, characterized in that: The mass ratio of each element in the Mg-Co-Ni-Fe active component compound is 1:1~2:1~2:1~3, and the Mg-Co-Ni-Fe active component compound accounts for 5~10% of the mass of the upper coating.

5. The three-way catalytic converter for gasoline engine exhaust purification according to claim 1 or 2, characterized in that: The Ce-Zr composite oxide is a cerium-zirconium solid solution, which contains 20-70% CeO2 by mass.

6. The preparation steps of the three-way catalytic converter for gasoline engine exhaust purification according to claim 5, characterized in that: The alumina is γ-alumina with a specific surface area of ​​100–200 m². 2 / g.

7. The three-way catalytic converter for gasoline engine exhaust purification according to claim 1 or 2, characterized in that: The salt additive is one or more of the salts corresponding to the elements Ba, La, Nd, Pr, Y, Sb, and Ti.

8. The method for preparing a three-way catalytic converter for gasoline engine exhaust purification according to any one of claims 1-7, characterized in that, The preparation steps include the following: Preparation and coating of the lower coating layer: Alumina, Ce-Zr composite oxide and salt additives are mixed with deionized water to prepare a slurry, which is then placed in a container and stirred. A soluble solution containing precious metals is added and stirred evenly to obtain a catalyst lower coating slurry. The lower coating slurry is coated onto a carrier and dried and calcined to obtain a semi-finished catalyst. Preparation of Mg-Co-Ni-Fe active component compound: According to the mass ratio of each element in the Mg-Co-Ni-Fe compound, soluble salts of Mg, Co and Fe are mixed and dissolved in deionized water to form a solution. An organic base is added to the above solution to completely precipitate Mg, Co and Fe. Then, soluble salts of nickel are added according to the ratio. After mixing and stirring evenly, the above mixture is placed in a microwave oven to dry, forming Mg-Co-Ni-Fe powder compound. (3) Preparation and application of the upper coating: Alumina, Ce-Zr composite oxide, Mg-Co-Ni-Fe powder compound and salt additive are prepared into a slurry and placed in a container for stirring. A soluble solution containing precious metals is added and stirred evenly to obtain the catalyst upper coating slurry. The upper coating slurry is coated on the semi-finished catalyst obtained in step (1) and dried and calcined to finally obtain the finished catalyst.

9. The preparation steps of the three-way catalytic converter for gasoline engine exhaust purification according to claim 8, characterized in that: The soluble solution containing precious metals in step (1) is a salt solution of Pd or Pt, and the soluble solution containing precious metals in step (3) is a salt solution of Rh.

10. The preparation steps of the three-way catalytic converter for gasoline engine exhaust purification according to claim 8, characterized in that: The drying and calcination conditions in steps (1) and (3) are: drying at 120-180℃ for 2-3 hours, and then calcining at 400-650℃ for 2-3 hours.